A theology of spatial justice in relation to land in South African History : 1856–2020. With reference to three South African congregations - Mlambo, Ntandoyenkosi Nomkhosi Nokuphiwa (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.